Infestation of ectoparasite of Probopyrus (Isopoda: Bopyridae) in Macrobrachium amazonicum (Caridea: Palaemonidae) in the Amazon River - Silva Duarte, Sting (2024)
Introduction: Macrobrachium amazonicum is widely distributed in South America, occurring in the Orinoco, Amazon and Paraguay river basins, being used as an important source of protein for feeding riverside populations. This prawn is host to the crustacean ectoparasites Probopyrus pandalicola, Probopyrus floridensis and Probopyrus bithynis (Bopyridae) that infest the gill cavity of the species. Objective: To report the prevalence and abundance of ectopasites (P. pandalicola, P. floridensis and P. bithynis) and the condition factor in M. amazonicum from the Amazon River, Eastern Amazon. Methods: The prawns were collected from May 2017 to April 2018, with the artisanal trap matapi in the municipalities of Mazagão (state of Amapá) and Santarém (state of Pará), Brazil. Results: 216 prawns infected with ectoparasites were captured, 133 in the Mazagão region (53 P. pandalicola, 48 P. bithynis and 32 P. floridensis) and 83 in the Santarém region (45 P. pandalicola and 38 P. bithynis). In Mazagão, the highest prevalence values were recorded in May (1.98 %) for P. floridensis, July (2.18 %) for P. bithynis, and March (1.93 %) for P. pandalicola. In the Santarém region, the highest prevalence values were recorded in February, 3.47 for P. pandalicola and 2.89 for P. bithynis. Regarding the abundance of parasites, there was no difference between the species grouped between the regions (t = 0.32, p = 0.739). Parasitized prawns from Mazagão and Santarém presented condition factors below expectations, with an average of 0.85 ± 0.55 for Santarém and 0.88 ± 0.44 for Mazagão. Conclusions: During the study it was found that P. pandalicola, P. bithynis and P. floridensis were present in M. amazonicum throughout the year. Furthermore, there was an effect of parasitism on M. amazonicum in the study areas.